Assessment of Invasive Alien Plant Species in Buffer zone and Indo-Nepal Border Area and their Impact on Native Biodiversity in Kanchanpur, Nepal - Bhatt, Divya; Saud, Roshani; Dhami, Dhiraj; Shakya, Bimala; Bhatt, Man Dev (Api Journal of Science, 2024)
IAPS are already a huge worldwide environmental issue, endangering biodiversity, altering ecosystems, and disrupting socioeconomic systems. The current study aimed to assess the distribution, diversity, and effect of IAPS in the Indo-Nepal buffer zones of Kanchanpur District, Nepal, with a focus on Bhimdatta and Dodharachadani Municipality. Between September 2023 and July 2024, a comprehensive field survey was undertaken at the research sites. Using quadrat sampling and herbarium identification, 21 plant species were identified. These species belonged to 11 families of which Asteraceae family was dominant in all study sites; holding 8 species. On the basis of IVI, 10 invasive plant species were recorded as dominant in all study sites. Of these, the highest importance value index of dominant invasive alien plant species at site 1 was recorded by Partheniun hysterophorus (41.39) and lowest by Mimosa pudica (2), whereas among dominant invasive alien plant species of site 2 the highest IVI was of Lantana camara (56.46) and lowest by Argemone maxicana (3.82). At site 3, the highest importance value index of dominant invasive alien plant species was recorded by Parthenium hysterophorus (28.35) and lowest by Bidens pilosa (2.85). The study's findings could have ecological and economic implications, such as loss of biodiversity, soil degradation, and health dangers. Furthermore, the study revealed the adaptive reproductive tactics of IAPS, such as allelopathy and seed viability, which increase their invasive nature. The findings highlight the critical need for focused management techniques to minimize the growing threat of IAPS, particularly in buffer zones where conservation efforts are currently underexplored.